Steering Hollow Multishelled Structures in Photocatalysis: Optimizing Surface and Mass Transport. Issue 44 (21st July 2020) - Wei, Yanze; Yang, Nailiang; Huang, KeKe; Wan, Jiawei; You, Feifei; Yu, Ranbo; Feng, Shouhua; Wang, Dan
Abstract: Hollow multishelled structures (HoMSs) provide a promising platform for fabricating photocatalysts, because the unique structure optimizes the effective surface and mass transport, showing enhanced light absorption, optimized mass transport and highly effective active sites exposed. Subsequently, the rational design on HoMS photocatalytsts is elaborated to boost the photocatalytic activity with efforts in all dimensions, from nanoscale to microscale. Breakthroughs in synthetic methodology of HoMSs have greatly evoked the prosperous photocatalytic researches for HoMSs since the developing of sequential templating approach in 2009. The dawn of HoMS photocatalyst is coming after revealing the temporal‐spatial ordering property, which is also discussed in this paper with pioneer works demonstrating the greatly enhanced energy/mass transfer processes. Some insights into the key challenges and perspectives of HoMSs photocatalysts are also discussed. With the reviewed fate and future of HoMSs photocatalysts, hopefully new concepts and innovative works can be inspired to flourish this sun‐rise field. Abstract : Following the principal line of energy/mass transfer processes in photocatalysis, the structural and compositional parameters affecting photocatalytic performance of hollow multishell structures (HoMSs) are discussed. Aiming at effective utilization based on HoMSs in photocatalytic reactions, the state‐of‐the‐art strategic methods are overviewed, along with a useful guidance for the future research directions of HoMS photocatalysts.